2016
DOI: 10.1159/000447236
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ivabradine versus β-Blockers for Heart Rate Reduction during Computed Tomography Coronary Angiography: A Meta-Analysis of Randomized Controlled Trials

Abstract: Objective: To quantify the efficacy of pretreatment with ivabradine compared to β-blockers before computed tomography coronary angiography (CTCA) via a meta-analysis of clinical randomized controlled trial data. Methods: We conducted a search for randomized controlled trials of pretreatment with ivabradine compared to β-blockers before CTCA in Medline, PubMed, Embase, SCI/SSCI/A&HCI, SAS Publishers, Web of Science, and the Cochrane Central Register. The Jadad quality score of the included studies, and the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Compared with beta-blockers, ivabradine showed significant effect on HR reduction during CTCA. Ivabradine also showed significant reduction in HR before CTCA without significant effect on BP 46 . Overall, these studies suggest that ivabradine is an attractive option for reducing HR in patients undergoing CTCA.…”
Section: Role Of Ivabradine In Different Cardiovascular Diseasesmentioning
confidence: 64%
“…Compared with beta-blockers, ivabradine showed significant effect on HR reduction during CTCA. Ivabradine also showed significant reduction in HR before CTCA without significant effect on BP 46 . Overall, these studies suggest that ivabradine is an attractive option for reducing HR in patients undergoing CTCA.…”
Section: Role Of Ivabradine In Different Cardiovascular Diseasesmentioning
confidence: 64%
“…The remaining studies showed a benefit in HR reduction and/or image quality with ivabradine including patients treated with and without concomitant β‐blockers 68,69,71–73,75,76,78,80,83 . A meta‐analysis of eight studies demonstrated ivabradine was superior to β‐blockers in lowering HR during the scan 84 …”
Section: Resultsmentioning
confidence: 99%
“…HR control medication, such as beta-blockers have long attempted to achieve this objective, but have numerous drawbacks and contraindications. However, newer drugs such as ivabradine, a funny channel blocker, have recently been successfully used and in studies proved more efficacious in lowering and stabilizing the HR (13)(14)(15). We, therefore, incorporated this into the protocol to establish the utility of a single dose of ivabradine in lowering the HR.…”
Section: Discussionmentioning
confidence: 99%